Influence of hydrothermal conditions with 200 °C and 15.5 bars on the properties of hardened HPC. (15th June 2015) - Abd Elrahman, Mohamed; Hillemeier, Bernd
Highlights: OPC concrete suffers strength decrease and durability loss after hydrothermal exposure. Combination of fine fly ash and slag cement stabilized the strength and enhances the durability. Chemical composition of the pore solution controls concrete behavior under hydrothermal treatment. Concrete stability is enhanced by using pozzolans and by reducing the w/b from 0.42 to 0.27. Abstract: In this paper, experimental investigations were carried out on the behavior of high performance concrete intended for a concrete tank to store hot water at temperature above 100 °C. The tested concrete has been subjected to heating–cooling cycles from ambient conditions to temperature up to 200 °C and pressure up to 15.5 bars. Several systems including ordinary Portland cement, slag cement, fine fly ash and silica fume have been tested. Experimental studies involving the measurements of strength, porosity and durability of concrete at normal conditions and after autoclaving for several cycles will be presented. The results indicated that OPC concrete suffered strength decrease and porosity increase as well as loss of durability after autoclaving for 50 cycles. However, the addition of fine fly ash stabilized the concrete and prevented the strength retrogression after hydrothermal exposure. Moreover, concrete porosity and durability are significantly enhanced by combination of fine fly ash with slag cement due to the formation of silica-rich C-S-H phases. These influences are more pronounced in mixes with low w/b ratio.